1997
DOI: 10.1073/pnas.94.10.5255
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of antigen-presenting activity of dendritic cells resulting from UV irradiation of murine skin is restored byin vitrophotorepair of cyclobutane pyrimidine dimers

Abstract: Exposing skin to UVB (280-320 nm) radiation suppresses contact hypersensitivity by a mechanism that involves an alteration in the activity of cutaneous antigenpresenting cells (APC). UV-induced DNA damage appears to be an important molecular trigger for this effect. The specific target cells in the skin that sustain DNA damage relevant to the immunosuppressive effect have yet to be identified. We tested the hypothesis that UV-induced DNA damage in the cutaneous APC was responsible for their impaired ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 38 publications
1
103
0
1
Order By: Relevance
“…Although there are many examples of UV exposure activating immune regulatory T cells (22, 44 -46), and evidence exists to indicate UV-damaged dendritic cells (16,17) can induce tolerance, a role for UV-activated B cells in tolerance induction is novel. This somewhat unexpected result may reflect the modification we used to induce tolerance in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many examples of UV exposure activating immune regulatory T cells (22, 44 -46), and evidence exists to indicate UV-damaged dendritic cells (16,17) can induce tolerance, a role for UV-activated B cells in tolerance induction is novel. This somewhat unexpected result may reflect the modification we used to induce tolerance in our system.…”
Section: Discussionmentioning
confidence: 99%
“…55 The importance of antigen presenting cells in the initiation of chronic GVHD was demonstrated in a murine allogeneic bone marrow transplantation model in which it was demonstrated that the initial targets for CD8 + T cells in GVHD were restricted to proteins expressed by residual host antigen presenting dendritic cells. 56 When host dendritic cells were eradicated by conditioning or replaced with donor dendritic cells, thus decreasing the interaction between host antigen-presenting cells and donor CD8 + cells, GVHD was attenuated.…”
Section: Importance Of Antigen Presenting Cells In Cgvhd Pathogenesismentioning
confidence: 99%
“…The incidence of nonmelanoma skin cancer, comprising of basal-and squamous-cell carcinoma, continues to increase in the United States, and solar UV, particularly its UVB (280-320 nm) spectrum, is the primary cause of these cancers and other cutaneous pathologies in the human population, more so in Caucasian individuals (Mukhtar and Elmets, 1996;Ananthaswamy et al, 1997;Greenlee et al, 2000;Jemal et al, 2000;de Gruijl, 2002). Exposure of mammalian skin to UV radiation alter cellular function via DNA damage (Vink et al, 1997;Katiyar et al, 2000), generation of reactive oxygen species (ROS) (Scharffetter-Kochanek et al, 1997;Katiyar et al, 2001a, b), activation and phosphorylation of mitogen-activated protein kinases (MAPKs), nuclear factor kappa B (NF-kB), and other signaling events (Iordanov et al, 1997;Chen et al, 1999;Katiyar and Mukhtar, 2001;Lefort et al, 2001;Bachelor et al, 2002;Hildesheim et al, 2002;Afaq et al, 2003a), and acts both as a tumor initiator and tumor promoter in animal models (Gensler and Welch, 1992;Katiyar et al, 1997). The UVB-induced activation of signal transduction pathways that control the expression of genes is responsible for its tumor-promoting effects (Huang et al, 1996;Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%